Pengembangan Aplikasi Scanning Barcode untuk Manajemen Stok pada Kantin Alwi College - Felix Gunawan; Fadhel Muhammad; Novan Wijaya (Universitas Multi Data Palembang, 2026)
Manual stock recording in small-scale canteens often causes data inaccuracy, inefficiency, and difficulties in monitoring inventory levels. This study aims to develop a barcode scanning-based application for inventory management at Alwi College canteen. The application enables administrators to identify items through barcode scanning and update incoming stock data automatically. The system was developed using the Agile methodology to support iterative development and continuous user feedback. UML diagrams were used to model the system, including use case, activity, sequence, and class diagrams. The results show that the application improves the accuracy and efficiency of stock recording, simplifies item classification, and supports real-time stock monitoring. Black box testing indicates that all main features function properly.